Polymerase Chain Reaction Based-Assays for Rapid Detection and Subtyping Of Type a Influenza Viruses - Chaharaein, Broomand (2006)
Highly pathogenic avian influenza (HPAI) virus causes high morbidity, mortality and still is a big threat in poultry industry. The recently raised awareness of the threat of a new influenza pandemic has stimulated interests in the development of a rapid detection method for influenza A viruses. In this study, four diagnostic methods for the detection of type A influenza viruses were explored. A conventional one-tube nucleoprotein reverse transcriptase polymerase chain reaction (NP RT-PCR) was developed for rapid detection of avian influenza A viruses. This method successfully detected 14 different haemagglutinin (HA) subtypes of different origins. A multiplex RT-PCR that successfully amplified three RNA templates of H5, H7 and H9 in one tube was also developed. The designed primers were specific in amplification of the HA genes of H5, H7 and H9 of type A influenza viruses. No amplification was observed with other avian infectious viruses such as Newcastle disease virus, infectious bronchitis virus and infectious bursa1 disease virus. An enzyme-linked immunosorbent assay (ELISA) detection method was then developed to detect the amplified PCR products. This method was 10 times more sensitive than the detection of PCR product using agarose gel electrophoresis. This method (RT-PCR-ELISA) was as sensitive as virus isolation in specific-pathogen-free (SPF) embryonated eggs. The detection limit of the RT-PCR-ELISA was compared with agarose gel electrophoresis and one-step SYBR Green I real time PCR. The RTPCR- ELISA was 10 times less sensitive than SYBR Green I real time PCR. The whole process for the detection of type A influenza virus and the avian H5, H7 and H9 subtypes, from extraction of RNA to analysis of PCR product by agarose gel electrophoresis or colorimetric assay can be completed within 6 h. It provides a rapid means of identification of the type and subtypes of influenza viruses and would be very useful for their surveillance. The advantage of using an ELSA reader is in removing any element of subjective interpretation as a source of error. The methods developed in this study, were tested on suspected cases. The finding indicated that the methods are rapid, sensitive and specific, and thus would be a method of choice for the surveillance of avian influenza virus. Moreover, the RT-PCR-ELISA method allows handling of a large number of samples and can be used in many diagnostic laboratories. Among the four methods developed, the SYBR Green I real time PCR was the best method in terms of sensitivity and specificity. This is followed by RT-PCR-ELSA, multiplex and conventional RT-PCR assays.